Returns and Volatility of Eurozone Energy Stocks - Ulrich Oberndorfer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper constitutes a first analysis on stock returns and stock return volatility of energy corporations from the Eurozone. According to our results, the gas market does not play a role for the pricing of Eurozone energy stocks. However, changes in the Euro to U.S. Dollar exchange rate as well as developments at the money and especially at the oil market strongly affect returns of the energy stock portfolios analyzed. While oil price hikes negatively impact on stock returns of European utilities, they lead to an appreciation of oil and gas stocks. Most importantly, we show that oil market volatility negatively affects European oil and gas stocks. In contrast, energy stock volatility is not driven by volatility of the resource market, but only by its own dynamics.
Keywords: Q43; C13; Q40; G12; 330; Energy stocks; resource prices; volatility; asset pricing; Energiewirtschaft; Börsenkurs; Rendite; Volatilität; Erdölpreis; Erdgasmarkt; EU-Staaten